Inheritance and potential use of grain color in the identification of genotypes resistant to pre-harvest sprouting in wheat - Santos,Lilian Tais dos (2010)
The inheritance of grain color and pre-harvest sprouting in wheat was studied to identify genotypes with high resistance to pre-harvest sprouting and evaluate the possible use of grain color in indirect selection of resistant lines. The genotypes of most lines were characterized with regard to the loci that control grain color. No significant correlations between grain color and pre-harvest sprouting resistance were observed, but correlations were useful when the frequency of segregating genotypes with white grain was relatively high. Of the eight F2:3 populations evaluated, only two differed significantly in grain sprouting between the white and red classes. Three genes for pre-harvest sprouting resistance seem to be present in the genotypes Frontana and Onix. Grain color should not be used as the only criterion for selecting wheat genotypes resistant to pre-harvest sprouting.